Pembelajaran Madzhab dalam Islam dan Implementasinya pada Pengajaran Menutup Aurat Bagi Siswi Kelas X-E SMAN 74 Jakarta - Witary, Aprillia Indah; Yusuf, M. Yunan (Fakultas Tarbiyah dan Ilmu Tarbiyah, Universitas PTIQ Jakarta, 2024)
Women are one of God's most glorified creations. Therefore, women are obliged to cover their private parts in order to maintain the honor that Allah has bestowed on them. For every Muslim woman who has reached the age of puberty, hiding or covering her private parts is mandatory. However, basically the majority of class X-E students at SMAN 74 Jakarta still do not implement this optimally. The aim of this journal is twofold: first, to find out how well the female students of X-E SMAN 74 Jakarta understand the importance of covering their private parts according to Islamic law; and second, increasing awareness of the importance of carrying out religious commands by finding out how well the female students of X-E SMAN 74 Jakarta understand the importance of covering their private parts according to Islamic religious law. This research uses descriptive qualitative research techniques based on field observations. It is believed that this research can be a reference source for readers, especially Muslim women, so that they always cover their private parts. This is in line with Islamic teachings, which aim to uphold high moral standards and maintain the privileges given to Muslims.